Anda di halaman 1dari 11

# Report and Opinion, 1(1), 2009, http://www.sciencepub.net, sciencepub@gmail.

com

68

Report and Opinion, 1(1), 2009, http://www.sciencepub.net, sciencepub@gmail.com The vibration of a uniformly simply supported beam carrying an arbitrary number of discrete masses m, m2, -----mN is considered. This mass mt is assumed to strike the beam at t = 0 and travel across it with velocity vit. The equations of motion, with damping neglected is written as
N 2y y 4y 2 y + EI 4 + Ky + = gf ( x, t ) mA + mi (u vi t ) 2 + cd t t x x 2 i =1

(1)

Where f (x, t)= i =1 EI = the flexural rigidity of the beam f (x,t) = the transverse deflection of the beam = the mass density of the beam material A = cross sectional area of the beam g = the acceleration due to gravity k = the foundation constant. L = the length of the beam

m (x v t )
i i

(2)

( x vi t ) is the Dirac delta function define to be zero everywhere except x=v t, i.e ( x vi t ) =0, x vi t and i
L 0 i

( x v t )dx = 1 in addition
The boundary conditions are Y (o, t) = Y (L, t) = 0 Yxx (o, t) = Yxx (L, t) = 0 Applying the Fourier finite sine transform, i.e =

(3) (4)

L 0
L

## 2y L L mx mx mx + Ky Yxx Sin dx + Sin = F ( x, t )Sin dx 2 0 0 0 L L L x

(6)

Solving equation (6) by integration by part, we obtained difference series solution which added together. The result becomes

EI

## m 4 4 m 2 2 N ( ) ( ) ( ) ( ) Z m , t p Z m , t Kz m , t MAZ m , t T + + + mi ( x vi t )Ytt (m, t ) tt 4 2 L L i =1

N

g m Sin = i i =1
Let

myit L m 4 4 m 2 2 p +K L4 L2

(7) (8)

Q = EI

=

(9)

(10)

69

## mvi t Z tt (m, t ) + K 5 Z t (m, t ) + K 6 Z (m, t ) = K 7 Sin

N i =1

(11)

3.0 Solution of the transformed equation. For the purpose of the solution we consider only one mass m traveling with velocity . The solutions for greater numbers of masses may be obtained in the same manner .Evidently the following special cases from equation 11 follow: (a) Moving force: - If we neglect the inertia term, we have the classical case of a moving force. Under the above assumption equation 11 becomes

## Z tt (m, t ) + K 5 Z t (m, t ) + K 6 Z (m, t ) = K 7 Sin

i =1

mvi t L

(12)

(b)

Moving Mass:-first approximation only the linear inertial term is considered, Equation 11 becomes.
N N i =1 i =1

## Z tt (m, t ) + K 3 mi Z tt (m, t ) + K 5 Z t (m, t ) + K 6 Z (m, t ) = K 7 Sin

(a) For moving force
N i =1

mvi t L

(13)

## Z tt (m, t ) + K 5 Z t (m, t ) + K 6 Z (m, t ) = K 7 mi Sin

Now solving equation for moving force, we have

mvi t L

## Z tt (m, t ) + K 5 Z t (m, t ) + K 6 Z (m, t ) = 0 This implies that Z ( m, t ) = Z c + Z p

For Zc; equation (12) becomes

(14)

## Z (m, t ) = e mt Z t (m, t ) = Me mt Z tt (m, t ) = M 2 e mt

M 2 e mt + K 5 Me mt = 0 e mt M 2 + K 5 m + K 6 = 0 e mt 0; thenM 2 + K 5 m + K 6 = 0

M =

M = M1 =

b b 2 4ac a = 1, b = K 5 andc = K 6 2a

K 5 K 52 4 K 6 2 K 5 + K 52 4 K 6 2
t

,M2 =

K 5 K 52 4 K 6 2

Therefore

zc = Aem1 + Bem2t
=

Ae

2 K5+ K5 4K6 t 2

+ Be

2 K5 K5 4K6 t 2

70

## Applying these boundary conditions Z (m, o) = 1 Zt (m, o) = 0

Ae 0 + Be 0 = 1 or A = 1 B A+ B =1
for Z (m,o) = 0;

(15)

Let
K
7

K + 5 =

K 52 4 K 2

and
K8

K 5 =

K 52 4 K 2

Z ( m , t ) = Ae K 7 t + Be K 8 t Z t ( m , t ) = AK 7 e K 7 t + BK 8 e K 8 t Z t ( m , o ) = AK 7 e 0 + BK 8 e 0 = 0 = AK 7 + BK 8 = 0
(16)

## Sub (15) in (16)

(1 B )K 7 + BK 8 = 0
K 7 BK 7 + BK 8 = 0 BK 8 BK 7 = K 7 B( K 8 K 7 ) = K 7 K7 B= K8 K7

Therefore

K7 A = 1 K K 7 8 K7 K8 or =1 + K8 K7 K8 K7
By expansion

A=

K5 2 K 52 4 K 6

K 52 4 K 6 2 K 52 4 K 6

A= A=

K5 2 K 52 4 K 6

1 2

K5 1 + 2 2 K 52 4 K 6 B = 1 A

71

## Report and Opinion, 1(1), 2009, http://www.sciencepub.net, sciencepub@gmail.com

K5 B = 1 1 + 2 2 K 2 4K 5 6
=

K5 1 + 2 2 K 52 4 K 6
2 K5 + K5 4 K6 t2

From Z c = Ae

+ Be
e

2 K5 K5 4 K6 t2

i.e. Z c = 1 +

K5 2 K 52 4 K 6

2 K5 + K5 4 K6 t2

K5 +1 2 2 K 2 4K 5 6

K5 e

2 K5 4 K6 t2

(17)

For Zp;

Z p = K g sin

mvi t L

Where K g = K 4

mi
i =1

Zp = A

Z tp =
Z ttp =

## sin mvt cos mvt +B L L

Am 2 2 v 2 t 2 mvt Bm 2 2 v 2 t 2 Sin cos mvt L L2 L2 Am 2 2 v 2 t 2 mvt Bm 2 2 v 2 t 2 mvt Bmvt Amvt Sin cos mvt + K 5 cos Sinmvt 2 2 L L L L L L mvt mvt mvt + K 6 A sin + B cos = K 9 Sin L L L sin mvt Z = K9 L sin mvt cos mvt +B Zp = A L L mvt mvt mvt mvt Z tp = A Sin cos B L L L L 2 2 2 2 2 2 2 2 Am v t mvt Bm v t mvt Z ttp = Sin cos 2 2 L L L L
The equation becomes

Am 2 2 v 2 t 2 mvt Bm 2 2 v 2 t 2 mvt mvt Bmvt mvt Amvt Sin Sin + K5 cos cos 2 2 L L L L L L L L mvt mvt mvt + K 6 A sin + B cos = K 9 Sin L L L

72

## Report and Opinion, 1(1), 2009, http://www.sciencepub.net, sciencepub@gmail.com

Am 2 2 v 2 t 2 BK 5 mvt mvt mvt = Sin + AK 6 Sin 2 L L L L 2 2 2 2 mvt Amvt Bm v t + + Sin K BK 5 6 2 L L L cos mvt mvt + K 9 Sin L L K5 1 + 1 2 2 K 2 4K x K + K 2 4K 5 5 6 5 6 2 m 2 2 v 2 t 2 mvt K9 K 2 6 L L + + 2 2 2 2 2 2 2 2 2 2 m v t m v t mvt 2 K6 + K5 L2 L2 L

(18)

## For, the solution Z (m,t) = Zc + Zp

K5 Z (m, t ) = 1 + 2 2 K 2 4K 5 6

x K 5 K 52 4 K 6 2

(20)

## m 2 2 v 2 t 2 K 5 mvt K K9 6 L2 x L 2 2 2 2 2 2 m 2 2 v 2 t 2 m 2 2 v 2 t 2 K m v t x 2 mvt 2 + K6 6 2 2 + K5 L2 L L L K5 K5 1 + 1 v (x, t) = 1 + 2 2 K 2 4K S K + K 2 4K 2 2 K 2 4K 5 6 5 5 6 5 6 2 m 2 v 2 t 2 K9 K 2 6 L 1 mvt + + 2 2 2 2 2 2 2 2 L S + m 2 2 v 2 t 2 2 2 2 2 S K 5 K 5 4K 6 m v t m vt 2 K6 + K5 L L2 2

m 2 2 v 2t 2 K9 K 6 L2 2 m 2 v 2 t 2 K 52 m 2 v 2 t 2 K 6 + L2 L2
(

K 5 mvt L 2 2 2 2 m K v t 6 L2

(21)

73

100 Z(m, t)

120

## 140 Fig. 2 Convergence of coefficient for moving mass solution

By using the same method for solving the equation for moving force i.e equation (13) for moving mass becomes:N N mvt Ztt (m, t )1 + K3 Mi + K5 Zt (m, t ) + K6 Z (m, t ) = K7 (m, t ) = K7 Sin (22) L i =1 i =1
N 1 + K 3 Mi = K 10 i =1

And let

mvt L

74

## K5 V(m, t) = 1 K10 + 2 2 K10 K 52 4 K10 K 6

K5 1 + 1 S K + K 2 4K K 2 2K K 2 4K K 5 5 10 6 10 5 10 6 2 K10

S K 5 K 52 4 K10 K 6 2 K10

m 2 2 v 2 t 2 K9 K 6 L2 + 2 2 2 2 2 2 2 2 2 m v t m v t + K5 2 K6 L L2 K 5 mvt L 2 2 2 2 K m v t 6 L2

mvt + 2 2 2 2 2 2 L S + m v t

m 2 2 v 2 t 2 K K9 6 L2 2 2 2 2 2 2 2 2 2 2 m v t K5 m v t K6 + L2 L2

(23)

While this equation is resistant to analytic technique, it yields readily to numerical procedures. For z (m,t), the solutions for m=1,2 are tabulated in table below Moving mass S/N 1 2 3 4 5 6 7 8 9 10 t 0.0 0.1 0.2 0.3 0.4 0.5 0.6 0.7 0.8 0.9 Z(1,t) 0.000 0.139 1.078 3.479 7.785 14.209 22.766 33.311 45.559 59.089 Z(2,t) 0.000 0.300 1.726 4.581 8.025 9.009 6.817 1.686 3.321 7.369

Table 1.0 moving mass Obviously higher approximations are possible by considering more terms of the series and following the same procedure. However, considering the rate of convergence of the lower-order solutions, it should not be necessary to continue this process. 4.0 Remark on the solution In a problem such as this, one is interested in the maximum amplitude of vibration and the condition under which is can occur. For the classical solution, Eq.20, it can been shown that under certain values of the velocity the condition of resonance occurs. In this case, the amplitude of vibration becomes a linear function of time. Fig.5. the maximum value of the amplitude, which occurs when the mass is at the end of the beam.

75

-10 -10

## 0.2 0.4 0.2 0.4

-20 -20
-40

0.6 0.6

0.8 0.8

1.0 1.0

1.2 1.2

1. 4 1. 4

t t

K5 = 0. 50 K6 = 1.75

z (m, t)

## -100 -100 -120 -120 K5 = 0. 75 K6 = 2.0 Moving Mass

Moving Force Moving Mass

Z(m, t)

-140 -140
Fig. 3 Comparison of solution

76

t 0

- 2
- 3
Z (m, t)

77